An Analysis Of Survival Strategies During The Covid-19 Crisis Based On Michael Porter's Strategic Framework - Wilen, Shareen Virginia; Adib, Noval (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to understand how PT. Using Michael Porter's strategic framework, Bina Busana Internusa survived during the COVID-19 pandemic. The research uses a qualitative method with a case study approach, where interviews were conducted with four key people, including managers and the company's COO. The results show that PT. Bina Busana Internusa focused on a cost leadership strategy during the crisis, while differentiation was mostly ignored because production had stopped due to the pandemic. This made it hard for the company to create unique products during that time. These findings support Michael Porter's theory about survival strategies in a competitive market. The study also suggests that the company should improve its digital capabilities and, when the situation gets better, focus on product innovation and expanding its market to become competitive again. The findings revealed that cost efficiency successfully reduced the company's losses compared to initial projections, making it a strategic reference for other companies facing similar challenges in the future.